EP.WE.490Influence of age on post-operative outcomes from adrenalectomy for phaeochromocytoma. (28th October 2021) - Mir, S A; Lansdown, M J; Collins, Emma; Fraser, Sheila
Abstract: Methods: A retrospective search of institutional databases for histologically and biochemically confirmed cases of phaeochromocytoma, at a single tertiary care institution, from 2012 to 2020. Clinical parameters, adrenal function, intra and postoperative data were obtained. Patients > 60 years were classified as elderly and outcome data within 30 days of operation compared to < 60 years. Results: Patients > 60 years constituted 31% (n = 17) of the cohort, mean age 70 ± 6 versus 43 ± 13 years for < 60 years (n = 38). There was no difference in tumour size, 4 ± 2.5 cm and 4.6 ± 2.6, p = 0.3. Frequency of laparoscopic resection was similar at 65% in both groups. Intra-operatively 5% of < 60 years required blood transfusion compared to none in > 60 years group with 12% in older group undergoing en-bloc resection and nephrectomy and 6% experiencing cardiac dysrhythmias. Postoperatively all patients were managed in level two care except 7% of < 60 years requiring level 3 care reflecting extent and complexity of resection. There was no difference in requirement and duration of vasoactive medication or length of stay in level 2, 1.6 ±1.2, 1.6 ±1.0 days. Proportion of patients graded ASA 3 in > 60 years was 53% compared with 41% in < 60 years. Postoperative complications in > 60 were 29% vs 13%, p = 0.003, with HAP being commonest. Length of hospital stay was also significantly longer at 5.8 ± 2.4 versus 4.5 ± 2.2, p = 0.02. There was no mortality. Conclusions: Age of the patient alone does not influence post-operative outcomes from adrenalectomy in phaeochromocytoma.